Insights into phylogenetic positions and distribution patterns: Complete mitogenomes of two sympatric Asian horned toads in Boulenophrys (Anura: Megophryidae) - Hongmei Xiang; Qiang Zhou; Wei Li; Juan Shu; Zhirong Gu; Wansheng Jiang (Ecology and Evolution, 2024)
Abstract Boulenophrys sangzhiensis and Boulenophrys tuberogranulata, two narrow‐distributed toad species within the Megophryidae family in southern China, are experiencing population declines due to habitat loss and degradation. Despite their critical conservation status, the two species remain largely overlooked in public and scientific spheres. This study presented the first sequencing, assembly, and annotation of the complete mitogenomes of both species using next‐generation sequencing. The mitogenome of B. sangzhiensis was 16,950 bp, while that of B. tuberogranulata was 16,841 bp, each comprising 13 protein‐coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), and a noncoding control region (D‐loop). The gene content, nucleotide composition, and evolutionary rates of each mitogenome were analyzed. Both mitogenomes exhibited negative AT skew and GC skew with high A + T content. ATP8 exhibited the highest evolutionary rate, while COI had the lowest. A phylogenetic analysis based on 28 mitogenomes revealed two major clades of Megophryidae, supporting the classification of two subfamilies, Megophryinae and Leptobrachiinae. Within the subfamily Megophryinae, the genus Boulenophrys was divided into two species groups. Intriguingly, despite coexisting in Zhangjiajie City, B. sangzhiensis and B. tuberogranulata exhibited distinct origins from the two different species groups, underscoring the unique role of the coexisting area Zhangjiajie in driving their speciation and preserving their current populations. A parallel pattern was also identified in the Leptobrachiinae genus Leptobrachium within the same region. This study provided valuable data references and enhanced our understanding of the molecular characteristics of these threatened amphibian species.